2021
DOI: 10.1200/jco.21.00899
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss After Radiation and Chemotherapy for CNS and Head-and-Neck Tumors in Children

Abstract: PURPOSE Hearing loss (HL) is a serious secondary effect of treatment for CNS and head-and-neck tumors in children. The goal of this study was to evaluate incidence and risk factors for HL in patients with multiple ototoxic exposures. PATIENTS AND METHODS We evaluated 340 ears from 171 patients with CNS or head-and-neck tumors treated with radiation, with or without chemotherapy, who had longitudinal audiologic evaluation. International Society of Pediatric Oncology-Boston grades were assigned to 2,420 hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…In our series, HL (≥Muenster 2b) was especially observed when the maximum dose to the cochlea exceeded 19 Gy. This observation is confirmed by previous studies [ 23 , 40 , 43 , 44 ]. Recently, Keilty et al (2021) [ 43 ] showed in patients with a brain tumour that the cumulative incidence of high-frequency HL (>4 kHz) was 50% or higher at 5 years after radiotherapy if the mean cochlear dose was >30 Gy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our series, HL (≥Muenster 2b) was especially observed when the maximum dose to the cochlea exceeded 19 Gy. This observation is confirmed by previous studies [ 23 , 40 , 43 , 44 ]. Recently, Keilty et al (2021) [ 43 ] showed in patients with a brain tumour that the cumulative incidence of high-frequency HL (>4 kHz) was 50% or higher at 5 years after radiotherapy if the mean cochlear dose was >30 Gy.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is confirmed by previous studies [ 23 , 40 , 43 , 44 ]. Recently, Keilty et al (2021) [ 43 ] showed in patients with a brain tumour that the cumulative incidence of high-frequency HL (>4 kHz) was 50% or higher at 5 years after radiotherapy if the mean cochlear dose was >30 Gy. Additionally, Hua et al (2008) [ 23 ] observed that the incidence of HL increased when the mean cochlear dose was greater than 40–45 Gy.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it has been shown that cisplatin-induced ototoxicity impairs cognitive outcome, which may also underlie this observation, and collectively, our results suggest that efforts to limit or omit cisplatin-related ototoxicity are required. 32,34-36…”
Section: Discussionmentioning
confidence: 99%
“…Proton therapy was generally unable to spare the cochlea due to the selection of beam arrangements that traversed the cochleae to treat the ventricular CTV. Higher cochlear RT dose is known to be associated with hearing decline, 23 though the contribution of chemotherapy (including carboplatin, which was used to treat patients enrolled in ACNS1123 stratum 1) also has an important effect 24 . Even when modest reductions of cochlear dose are attained, such as in children treated with proton therapy for medulloblastoma, improvements in hearing function may be difficult to detect due to other ototoxic risk factors 25 .…”
Section: Discussionmentioning
confidence: 99%